Faulkner ed Hemingway. Due nobel americani - Turi, Nicola (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2009)
Faulkner and Hemingway can probably be considered the greatest American writers of the twentieth century. In the mid 1960s, Fabbri entrusted the task of addressing their work and style to the militant critic Ruggero Jacobbi, who had shortly returned to Europe after a period of voluntary exile in Brazil. The two resulting volumes became pendant pieces in a unified meditation on the motives and movements of true poetry. Having become practically impossible to get hold of, Firenze University Press is now republishing them in the same format, preceded by an introduction by Nicola Turi. Thus the critical opus of Jacobbi is enriched with another bibliographical entry, made available once more through a painstaking operation of retrieval promoted by Anna Dolfi and furthered through the kind assistance of Ruggero's wife Mara Jacobbi. The portrait that emerges continues to be that of an intellectual gifted with extraordinary versatility, capable of delivering unforgettable critical insights on every page.